FROM SELF-EFFICACY TO SPEAKING PROFICIENCY: INVESTIGATING THE CORRELATION BETWEEN SELF-EFFICACY AND SPEAKING SKILL - Gayatri, Ni Luh Putu Ita; Mahardika, I Gusti Ngurah Agung Wijaya; Phalaguna, Ida Bagus Gde (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Speaking proficiency is a crucial component of English language learning, particularly for students preparing to become future English teachers. However, many learners face challenges in developing oral competence due to low confidence and limited self-efficacy. This study investigates the correlation between speaking self-efficacy and speaking skill among fourth-semester undergraduate students of the English Language Education Department (ELED) at I Gusti Bagus Sugriwa State Hindu University Denpasar. A total of 65 students participated as respondents. The research employed a quantitative correlational design, using a self-efficacy questionnaire to measure students’ beliefs about their speaking abilities and a speaking test to assess their oral performance. Data were analyzed using Pearson’s product-moment correlation. The findings revealed a statistically significant but low positive correlation (r = .302, p = .015) between speaking self-efficacy and speaking skill. This suggests that while self-efficacy contributes to speaking performance, it is not the only factor influencing students’ oral competence. Other variables such as motivation, anxiety, and exposure to authentic communication may also play an important role. The study concludes that fostering students’ speaking self-efficacy through supportive learning environments and communicative activities can enhance their speaking skills and better prepare them for their future roles as English teachers.